Virology Downunder, a meeting commentary from the 2019 Lorne Infection and Immunity Conference, Australia - Gregor Ebert; Prasad N. Paradkar; Sarah L. Londrigan (Virology Journal, 2019)
Abstract The aim of this article is to summarise the virology content presented at the 9th Lorne Infection and Immunity Conference, Australia, in February 2019. The broad program included virology as a key theme, and the commentary herein highlights several key virology presentations at the meeting.